I own the land, do i own the airspace as well? - Mohamad, Nor Asiah (2008)
Section 44 of the National Land Code 1965 provides for the exclusive use and enjoyment of land by any registered owner. In addition, s 340 state the indefeasibility of registered land titles and dealings. The question is: Is it legitimate to regard the airspace above owned land the owner's legitimate property which he/she can utilize and enjoy freely? Has the land owner sufficient proprietary right and interest of the airspace above his land which would entitle him defend his rights against any person who encroaches his/her rights and interests? This paper seeks to examine the law and policy pertaining to yhe right to enjoy the airspace above one's land, and tries to determine whether this kind of right of enjoyment is unlimited, i.e. whether the owner can dispose his right and interest over the airspace gives rise to many legal issues which require legal practitioners to consider existing policies and find legal solutions.